A Comment on Assortative Matching at the Top of the Distribution: Evidence from the World's Most Exclusive Marriage Market (2022) - Lamis Kattan; Lili Mark; Louis-Philippe Morin; Wenjie Tian (Institute for Replication (I4R), 2023)
Goni (2022) relies on a novel data on peerage marriages in Britain to ex- amine the impact of matching technology on marital sorting. He relies on the London Season interruption (18611863) as a natural experiment that raised search costs and reduced market segregation. In his preferred specification, he exploits exogenous variation in women's probability to marry during the interruption for their age in 1861 and finds that the interruption increased the probability of marrying a commoner; reduced the probability of marrying an heir, increased the difference in spouses' family landholdings (in absolute value); decreased the difference in spouses' family landholdings (husband - wife); and increased the likelihood of never getting married (See Table 2, columns 1 to 6, respectively). First, we reproduce the paper's main findings and find no coding errors. Second, we test the robustness of the results to (1) the use of additional fixed effects and (2) sample restrictions. Finally, we examine the heterogeneous effects of this interruption by age and year. We find that original estimates are robust and are not significantly affected using these alternative specifications.
Keywords: 330